Molecular and morphological studies reveal a new species of Panaeolus (Agaricales, Basidiomycota) from Punjab, Pakistan - Asif, Muhammad; Firdous, Qudsia; Izhar, Aiman; Niazi, Abdul Rehman; Sarwar, Samina; Khalid, Abdul Nasir (European Journal of Taxonomy, 2023)
Panaeolus punjabensis M. Asif, Q. Firdous, A. Izhar, Niazi & Khalid sp. nov. was collected from three different localities (Bahawalnagar, Kasur, and Lahore) in Punjab, Pakistan. Morphological observations and phylogenetic analyses based on nuclear encoded internal transcribed spacers (ITS1-5.8S-ITS2 = ITS) and D1/D2 domain of large subunit (28S) rDNA confirmed the taxonomic distinctness of this species. The new species is potentially hallucinogenic and characterized by a parabolic pileus with a light brown center, broadly fusiform basidiospores, presence of cheilocystidia, pileocystidia, and caulocystidia, and absence of pleurocystidia and clamp connections. The DNA sequences of the species clustered together in a well-supported distinct clade. We present a detailed description, photographs, and line drawings, and elucidate and discuss the phylogenetic position of the new species. Morphological comparisons with phylogenetically and morphologically allied species are discussed.